Neoliberal Higher Education Discourse in the Context of University Mergers in Lithuania - Bružienė, Rūta (Acta Paedagogica Vilnensia, 2025)
University mergers are closely linked to the neoliberal higher education discourse which relies on competitiveness and the adoption of best market practices in institutional settings. The necessity of a second wave of university mergers has been dictated by the neoliberal order of higher education. The drive for greater competitiveness, more efficient system management and a better response to societal needs through university mergers coincides with the neoliberal higher education discourse. While mergers are not a new practice, they are often chosen as a policy instrument precisely because of the neoliberal conditions under which the system is organised. Therefore, the aim of the paper is to investigate how neoliberal discourses have been used to shape the perception of the need for university mergers in Lithuania.The analysis of online media messages related to university mergers (2005–2020) reveals that university mergers are an integral part of the discussions on other structural reforms of higher education, such as governance or funding. University mergers are framed as an imminent and obligatory solution to a wide range of higher education problems, mainly targeting discourses on study quality and international competitiveness. And while the arguments seem to remain similar over time, the content of both quality and competitiveness concepts is changing. Initially, quality was associated with standard setting and societal needs, with a later shift towards internationalisation and the labour market needs. The notion of competitiveness is also changing, from seeking to attract more domestic students, to the vision of attracting high-level academics and students from abroad, becoming regional or even European leaders and reaching top rankings.
Keywords: university mergers; Neoliberalism; frame theory